Linking global leadership to domestic legitimacy: Comparative analysis of perceptions of Xi and Obama. (13th August 2021) - Kim, Myunghee; Cao, Xiongwei
Abstract: Objectives: As a one‐party state, the legitimacy of the Chinese Communist Party rule and the leader, Xi, stems from unique sources. This article examines those sources of legitimacy in China and compares those with the United States and its leader, President Obama. Methods: Data from the 2014 Pew Global Attitude Survey are analyzed using ordered logistic regressions to test three main hypotheses: the vertical trust leakage hypothesis, the new Cultural Revolution hypothesis, and the parallel upward mobility hypothesis. Results: Xi's anti‐corruption efforts against governmental officials create perceptions of Xi as a moral leader who protects citizens from corrupt local officials. Growing censorship in China prevents intellectuals from questioning Xi's power. The Chinese Dream campaign spearheaded by Xi blends nationalism and populism. Conclusion: The findings suggest that Xi's strategy to portray him as a moral leader, the suppression of intellectuals and advocacy of the Chinese Dream campaign yields strong confidence from Chinese citizens.